PENGARUH LATIHAN HEADING SECARA BERGANTIAN TERHADAP KETERAMPILAN HEADING PADA TIM SEPAK BOLA SMP BABUSSALAM PEKANBARU - Neno Tri Sukardi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the effect of exercise heading in shifts of skills heading the soccer SMP Babussalam Pekanbaru . In this study researcher took population of the football SMP Babussalam Pekanbaru, amounting to 16 people. The researcher used the total sampling technique of saturated sample where all population sampled. The design of this study used pretest-posttest approach. Instrumen l’ve done in this study to gauge the skills heading with how to play the ball with my head. After that, the data were processed by statistics, to test the normality by lilifors test at a significant level of α (0.05). The hypothesis proposed is the effect of exercise heading in shifts of skills heading . Based on statistical data analysis, it yields pretest data Lcount 0,1728, data posttest Lcount 0,1956 and Ltabel 0,213, mean Lcount < Ltabel. Then the data is normally distributed. Based on t test analysis yielded Tcount equal to 6,25 and Ttabel 1,75, mean Tcount> Ttabel . Thus, we can concluded that there are Effect of heading in shifts of skills heading the soccer SMP Babussalam Pekanbaru.Keywords: Heading in shifts , Skill heading